PRMT6 inhibitors promote fracture healing by modulating osteoclast glucose metabolism - Wu, Nan; Wang, Renkai; Nian, Shensheng; Zhang, Hao; Zhou, Panyu; Tang, Hao (Frontiers in Immunology, 2025)
IntroductionImpaired fracture healing remains a significant clinical challenge due to the complexity of the healing process. Osteoclasts, derived from monocytes, are pivotal in bone tissue reconstruction, yet no effective clinical tools exist to promote fracture healing by modulating osteoclast activity.MethodsWe investigated the role of Protein Arginine Methyltransferase 6 (PRMT6) in fracture healing, focusing on its regulation of osteoclast glucose metabolism. PRMT6 deficiency and pharmacological inhibition were employed to assess its functional impact.ResultsPRMT6 was found to promote osteoclastogenesis and activate glycolysis. Both genetic deficiency and pharmacological inhibition of PRMT6 suppressed osteoclast formation and glycolytic activity. Further, PRMT6 inhibitors significantly enhanced fracture healing in vivo by inhibiting osteoclastogenesis.DiscussionOur study identifies PRMT6 as a key regulator of osteoclast metabolism and fracture repair. Targeting PRMT6 offers a novel therapeutic strategy for impaired fracture healing and provides new insights into the mechanisms of bone tissue regeneration.